Penerapan LKPD Operasi Penjumlahan dan Pengurangan Bilangan Bulat Berbasis Problem Solving - Amanda Prasasti; Depriyanti Depriyanti; Eka Yulianti; Syutaridho Syutaridho (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to describe students' mathematical understanding abilities through the application of a problem solving approach using magic coin media on integer operation material. This study is a qualitative study with a descriptive approach conducted at MTs An-Nuur Palembang in May of the 2025/2026 academic year. The subjects of the study were 25 grade VII students who were selected purposively. Data collection was carried out through observation, documentation, and learning outcome tests. The results of the study showed that the use of magic coin media in mathematics learning was able to improve students' conceptual understanding. This media helps students to be more active, understand integer operations concretely, and be involved in the problem-solving process independently or in groups. These findings indicate that the problem solving approach combined with magic coin media can create a fun learning atmosphere, and is effective in improving students' mathematical understanding abilities.